Supersensitivity and Subsensitivity of the β-Adrenergic Receptor in Pineal Gland Regulated by Catecholamine Transmitter - Deguchi, Takeo (1973)
Depletion of neural norepinephrine by reserpine treatment or by denervation resulted in a greater induction of serotonin N-acetyltransferase (EC 2.3.1.5) and a higher elevation of cyclic AMP in postsynaptic pineal cell to small amount of isoproterenol. This increase in responsiveness occurs rapidly within 24 hr after treatment with reserpine. Repeated administration of isoproterenol to the denervated or reserpine-treated rats not only suppressed the superinduction, but also caused a decreased response to isoproterenol in cultured pineal cells. Cultured pineal cells from denervated or reserpine-treated rats were about 10 times more responsive to small amounts of isoproterenol. The response of cultured pineal cells of rats which were repeatedly injected with isoproterenol was markedly reduced after exposure to submaximal amounts of catecholamines. The maximal increase in N-acetyltransferase was the same in denervated, reserpine-treated, isoproterenol-treated, and untreated pineal cells. Exposure of rats to continuous lighting (a procedure that reduces sympathetic nerve activity) resulted in a superinduction of pineal N-acetyltransferase by isoproterenol. These observations indicate that the responsiveness of the postsynaptic β-adrenergic receptor is conditioned by prior exposure to its agonist, norepinephrine. Decreased norepinephrine results in supersensitivity, and repeated exposure to large amounts of catecholamines causes subsensitivity (tolerance).